UPAYA PEREMAJAAN DAN PENYERAPAN LOGAM MINYAK GORENG BEKAS INDUSTRI MAKANAN TRADISIONAL DENGAN MEMANFAATKAN BIOADSORBEN TANDAN KOSONG KELAPA SAWIT (TKKS) - Susi Desminarti; Edi Joniarta (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2007)
The research has been carried out in the Processing and Chemistry Laboratory of Politeknik Pertanian Negeri Payakumbuh and Post Harvest Laboratory in Bogor since July until November 2006. The research objectives was to prolong the using time of used cooking oil on food industries through applying the empty fruit bunch of palm bioadsorbent. The optimum condition of TKKS applied were 125 mm size and 5% bioadsorben from the weight of oil (Desminarti dan Rahzarni, 2004). The prolonging of cooking oil application can be done throughrefining used cooking oil so that the part of bad cooking oil can be lremoved. Statistical design used in this research was Completely Randomized Design with four treatments dan three replications. If the result was significant it will be followed by DMRT test on 5% significant level. Based on the experiment could be concluded that that four times titration could produced the oil based on SNI criterya in the relation to the water content (0.23%), peroxide value (0.82%) and free fatty acid value (0.23%) and it could also decrease Fe content from 76ppm to 22 ppm, Cu from 1.2 ppm to 0.40 ppm and Non Urea Adduct Forming (NAF) from 126 ppm to 102 ppm. The bioadsorbent sorption content on water varied from 78% to 80%; peroxide value from 14.71 to 59.80%, free fattyacid from 55.61 to 89.25%, Fe from 68.42 to 71.05%, Cu from 5% to 60% and NAF from 17.46 to 19.05%.